2011
DOI: 10.1016/j.neuroimage.2011.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound modulates region-specific brain activity

Abstract: We demonstrated the in vivo feasibility of using focused ultrasound (FUS) to transiently modulate (through either stimulation or suppression) the function of regional brain tissue in rabbits. FUS was delivered in a train of pulses at low acoustic energy, far below the cavitation threshold, to the animal's somatomotor and visual areas, as guided by anatomical and functional information from magnetic resonance imaging (MRI). The temporary alterations in the brain function affected by the sonication were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
524
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(560 citation statements)
references
References 34 publications
27
524
7
2
Order By: Relevance
“…Although these studies clearly demonstrate neurostimulation, there was little control over the spatial extent of the stimulation, which was generally quite large (ϳ2 mm lateral). In a similar study using "focused" US that activated rabbit motor cortex measured by fMRI and behavior, the size of the acoustic focus was estimated to be 2.3 mm in diameter and 5.5 mm in length (Yoo et al, 2011). Finally, recent work has shown the feasibility of in vivo retinal stimulation (Naor et al, 2012) .…”
Section: Toward High-resolution Patterned Us Neurostimulationmentioning
confidence: 98%
“…Although these studies clearly demonstrate neurostimulation, there was little control over the spatial extent of the stimulation, which was generally quite large (ϳ2 mm lateral). In a similar study using "focused" US that activated rabbit motor cortex measured by fMRI and behavior, the size of the acoustic focus was estimated to be 2.3 mm in diameter and 5.5 mm in length (Yoo et al, 2011). Finally, recent work has shown the feasibility of in vivo retinal stimulation (Naor et al, 2012) .…”
Section: Toward High-resolution Patterned Us Neurostimulationmentioning
confidence: 98%
“…15,25,26,70,86 Other studies have demonstrated activation of neural tissue, both peripherally and in the CNS. 32,50,81 These effects have been postulated to occur as a result of mechanical stimuli (reversible) and thermal ablation (potentially irreversible).…”
Section: Neuromodulation and Epilepsymentioning
confidence: 99%
“…Как лабора-торные исследования на животных, так и некоторые со-временные доклинические исследования свидетельству-ют о способности ФУЗ вызывать in vivo контролируемые нейромодулирующие -стимулирующие и ингибирую-щие эффекты [66][67][68][69][70][71][72][73][74]. УЗ низкой интенсивности не приводит к изменению температуры в мишени и вокруг нее, а также, по результатам гистологических исследова-ний, не вызывает явных повреждений в тканях.…”
Section: недеструктивная нейромодуляцияunclassified